Taxonomic revision of Bergera J.Koenig ex L. (Rutaceae) based on the molecular phylogeny and morphology - Mou, Feng-Juan; Hu, Xiu; Ha, Bui Thu; Cuong, Nguyen Manh (European Journal of Taxonomy, 2023)
Several phylogenetic studies have revealed that Murraya s. lat. is not monophyletic, suggesting that it should be split into two genera, namely Murraya s. str. and Bergera J.Koenig ex L. Here, the genus Bergera is comprehensively revised based on molecular and morphological data. The genus consists of 11 species in total, including all species previously placed in Murraya sect. Bergera and an additional species previously placed in Murraya sect. Murraya. Ten new combinations are proposed, namely Bergera alternifolia (Kurz) F.J.Mou comb. nov., B. crenulata (Turcz.) F.J.Mou comb. nov., B. euchrestifolia (Hayata) F.J.Mou comb. nov., B. glabra (Guillemin) F.J.Mou comb. nov., B. kwangsiensis (C.C.Huang) F.J.Mou comb. nov., B. macrophylla (C.C.Huang) F.J.Mou comb. nov., B. microphylla (Merr. & Chun) F.J.Mou comb. nov., B. siamensis (Craib) F.J.Mou comb. nov., B. stenocarpa (Drake) F.J.Mou comb. nov., and B. tetramera (C.C.Huang) F.J.Mou comb. nov. An identification key of the 11 species and morphological descriptions are provided, as well as illustrations of diagnostic characteristics. Phylogenetic relationships of the species in Bergera are discussed.